The hidden heart of autoimmunity: a scoping review of carditis in rheumatoid arthritis and IgG4-related disease - Sharma, Rachit Y.; Modi, Kaumil T.; Patel, Malav S.; Patel, Krimaben I.; Memon, Shadin A. (International Journal of Research in Medical Sciences, 2025)
Cardiac involvement in autoimmune diseases is often more common and more serious than we tend to acknowledge. While most clinicians are familiar with the joint pain of rheumatoid arthritis or the organ swelling of IgG4-related disease, inflammation of the heart itself is frequently missed. This is partly because cardiac symptoms are subtle or mistaken for something else, and partly because cardiovascular issues simply aren’t top of mind when managing autoimmune patients. As a result, carditis whether it’s myocarditis, pericarditis, or pancarditis remains underdiagnosed, underreported, and under-discussed, especially in the context of rarer conditions. This gap in recognition is particularly noticeable in IgG4-related disease, a condition known for causing fibrotic masses and multiorgan inflammation, but where cardiac involvement is poorly documented and often misclassified. Even in rheumatoid arthritis (RA), a disease much more common and much better studied, direct inflammation of the heart is often overshadowed by more visible symptoms like synovitis or systemic fatigue. Yet, evidence suggests that cardiac complications significantly contribute to both morbidity and mortality in autoimmune patients, often silently progressing until they become life-threatening. This scoping review sets out to bring more attention to this overlooked aspect of autoimmune disease. We aim to explore and organise the current literature on carditis in RA and IgG4-related disease, looking closely at how it presents, how it’s diagnosed, what mechanisms might be driving it, and how it’s treated. We’ve taken a wide lens to capture everything from well-documented case reports and cohort studies to emerging data on biomarkers and imaging techniques. In the end, this review is not just about summarising the science. It’s about bringing the heart back into the conversation, literally and figuratively when we talk about autoimmune diseases. Because if we want to improve outcomes for these patients, we need to start looking beyond the obvious and paying closer attention to what’s happening inside the chest.